Penentuan kadar Arsen dan Besi dalam tepung serat sawit yang telah dipucatkan menggunakan HClO4 dan arang dari limbah pabrik kelapa sawit - Abu Bakar (Pendidikan Kimia FKIP Universitas Jambi, 2009)
The effect of HC1O4 and HC1O4 mixed with charcoal toward Fe containing in the fibrous part of palm oil powder have been investigated. Firstly the flour was prepared from the fibrous part of palm oil which slices and 50 g of it macerated in NaOH 2 M for 2 h followed with washing and maceration again with variation concentration of HClO4 and charcoal; (2% :10g), (4% :20g), (6% :30g), (8% :40g), (10% :50g). It was ground into the flour. Fe containing in the fibrous part of palm oil powder without treatment was 189.15 ppm. Treatment of HClO4 and charcoal appeared could afford to decrease the amount of Fe. The minimum level of Fe was found out at ratio 4% :20g gave the amount of Fe 25.4 ppm while the highest reduction of Fe level at 10% :50g was 82 ppm. Arsenic content in the fibrous part of palm oil powder was not detected neither treated with HC1O4 nor without treatment.